Fault Diagnosis Technology for Auxiliary Converter Unit - 王佳佳; 刘长清 (Kongzhi Yu Xinxi Jishu)
It introduces a fault diagnosis of auxiliary converter, and then emphatically analyses the main circuit of the converter and the structures of hardware and software for the diagnosis technology. It has been applied on many types of auxiliary converters. The actual operation indicates that the technology is practical and reliable, which can effectively assist in analyzing the faults of auxiliary converter.